Impact of CAP’s pillars on Romanian rural employment - Vincze, Maria; Kerekes, Kinga (Applied Studies in Agribusiness and Commerce, 2009)
This paper aims to clarify the direction of change in rural employment on short- and medium term in Romania, while CAP regulations are being introduced and the global economic crisis emerges. First we put into evidence the decrease of the role of agriculture as buffer for unemployment and the poor contribution of non-agricultural activities to provide employment for rural residents.Then we analyse the main characteristics of the rural labour force. Finally we synthesize the opinions expressed by 33 consultants (working at the Offices for Agricultural Consultancy from different counties in Transylvania) about the estimated short term evolution of rural employment and the impact of CAP on Romanian rural areas.